1994
DOI: 10.1007/bf00386579
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of cancer mortality at a transformer-assembly facility

Abstract: To address earlier reports of excess cancer mortality associated with employment at a large transformer manufacturing plant, each plant operation was rated for seven exposures: Pyranol (a mixture of polychlorinated biphenyls and trichlorobenzene), trichloroethylene, benzene, mixed solvents, asbestos, synthetic resins, and machining fluids. Site-specific cancer deaths among active or retired employees were cases; controls were selected from deaths (primarily cardiovascular deaths) presumed to be unassociated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…The findings from the case-control studies (54)(55)(56)(78)(79)(80)83,84) shown in Table 12 add further support for an association between solvents, specifically TCE, and nonHodgkin's lymphoma. Six of seven studies showed elevated ORs, two were statistically significant, and several reported TCE (rather than general solvent) exposure.…”
Section: Community-based Studiesmentioning
confidence: 81%
See 2 more Smart Citations
“…The findings from the case-control studies (54)(55)(56)(78)(79)(80)83,84) shown in Table 12 add further support for an association between solvents, specifically TCE, and nonHodgkin's lymphoma. Six of seven studies showed elevated ORs, two were statistically significant, and several reported TCE (rather than general solvent) exposure.…”
Section: Community-based Studiesmentioning
confidence: 81%
“…In addition to several reviews human evidence evidence (13). (115) and Swaen (116) about the design of their study (10), calculate the combined OR among six case-control studies (60)(61)(62)(63)(64)83) McLaughlin and Blot (116) subsequently review the epidemiology of TCE and kidney cancer in seven cohort studies (10,18,19,24,30,31,104) and six case-control studies (57,(60)(61)(62)83,84) In their discussion, they fail to distinguish results either between men and women or incidence and mortality, and argue that none of the cohort studies except "the methodologically questionable" Henschler et al. study (10) The newest data on kidney cancer suggest different interpretations, although Weiss (6) and McLaughlin and Blot (117) caution the reader on the interpretation of these results because the Tier I cohort studies they had available showed, at best, a weak response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three US studies included aerospace or aircraft worker cohorts [22][23][24], while four European studies included cohorts of workers from various occupational groups who were exposed to TCE [26][27][28][29]. In a case-control study of US transformer manufacturing plant workers, Greenland et al [25] presented results for leukaemia, based on TCE job exposure matrices Historical measurement files were used to select TCE-using industries. The primary industries representing the cohort of workers were iron and metal, followed by electronics and painting Hansen et al,…”
Section: Resultsmentioning
confidence: 99%
“…Elevated risk ratios (RR) were found for nonwelding metal workers (RR 1.70) and for stainless steel grinders (7 observations, RR 2.85) in a retrospective cohort study of Danish metal workers [Stagis Hansen, 1990]. In contrast, exposure to machining fluids did not appear to increase the risk of lung cancer in a cohort of more than 5,000 metal machinists [Decouflé, 1978], or in workers at a transformerassembly facility [Greenland et al, 1994]. Swedish metal workers exposed to oil mists [Jarvholm and Lavenius, 1987], bearing plant workers exposed to a variety of cutting fluids , and Finnish machine shop workers [Tola et al, 1988] were also found to have levels of lung cancer risk comparable to those of referent groups.…”
Section: Introductionmentioning
confidence: 89%